2015
DOI: 10.5507/bp.2015.025
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced chemoresistance in cancer cells: The role of not only HIF-1

Abstract: Background. The aim of this review is to provide the information about molecular basis of hypoxia-induced chemoresistance, focusing on the possibility of diagnostic and therapeutic use. Results. Hypoxia is a common feature of tumors and represents an independent prognostic factor in many cancers. It is the result of imbalances in the intake and consumption of oxygen caused by abnormal vessels in the tumor and the rapid proliferation of cancer cells. Hypoxia-induced resistance to cisplatin, doxorubicin, etoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 162 publications
1
72
2
1
Order By: Relevance
“…Кроме того, растущий объем экспериментальных данных свидетельствует о том, что в некоторых типах злокачественных образований положительные эффекты CPt заметно уменьшались в связи с условиями гипоксии. Многие из HIF-1 ин-дуцибельных молекул, таких как ростовые факторы, транспортеры (Glut-1, Mdr-1), антиапоптотический белок Bcl-2, прямо или опосредованно могут участво-вать в развитии резистентности к химиотерапевтиче-ским препаратам [25].…”
Section: Discussionunclassified
“…Кроме того, растущий объем экспериментальных данных свидетельствует о том, что в некоторых типах злокачественных образований положительные эффекты CPt заметно уменьшались в связи с условиями гипоксии. Многие из HIF-1 ин-дуцибельных молекул, таких как ростовые факторы, транспортеры (Glut-1, Mdr-1), антиапоптотический белок Bcl-2, прямо или опосредованно могут участво-вать в развитии резистентности к химиотерапевтиче-ским препаратам [25].…”
Section: Discussionunclassified
“…HIF1A is the central node that mediates activation of a number of different signaling pathways that alter metabolic pathways, induce invasiveness, promote chemoresistance, and lead to a poor prognosis of the patient 46 . HIF has been reported to participate in drug and radiotherapy resistance in cancer treatment.…”
Section: Hypoxic Microenvironment As a Factor For Chemoresistancementioning
confidence: 99%
“…Indeed, we found that two gene sets involved in drug resistance were significantly enriched in the low-score phenotype. Hypoxia is commonly observed in many solid tumors including HNSCC, and is linked to chemo-resistance (19,20). Our results revealed that the low-score subtype was significantly enriched by a hypoxia-induced gene set in HNSCC (21).…”
Section: Main Effect Of Variablesmentioning
confidence: 99%